Corporate Board Structure, Managerial self-Dealing, and Common Agency - Vinicius Carrasco (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2006)
Corporate Boards usually come in two different shapes: unitary and dual. In the former, a single board/principal is responsible for monitoring and establishing performance targets; in the latter, these tasks are split between two boards/principals. This paper compares these two arrangements in terms of corporate performance and managerial self-dealing for a situation in which the CEO has private information. The equilibrium set of the common agency game induced by the dual board structure is fully characterized. Compared to a single board, a dual board demands less aggressive performance targets from the CEO, but exerts more monitoring. An unambiguous consequence of the first feature is that the CEO always exerts less effort toward production with a dual board. Due to the reduction in performance targets, the effect of a dual board on CEO's self-dealing is ambiguous: there are equilibria in which, in spite of the increase in monitoring, self-dealing is higher in a dual system..
Keywords: 330; Aufsichtsrat; Vorstand; Organisationsstruktur; Informationsökonomik; Corporate Governance; Theorie